(untitled) (Journal of Economic Research & Business Administration, 2016)
Modern industry of tourism is one of the largest profitable and dynamically developing segments of the international trading in services. Acuestss from tourism steadily occupy the third place – after acuestss from the export of oil, oil products and cars. Kazakhstan possesses large possibilities of the valuable including to the world tourist market and to occupy the niche. From data of Worldwide tourist organization, tourism provides tenth part of world gross national product, over 11%% international investments, every 9th workplace, are in a world production. For development of strategy of development of home tourism and project of cluster Government and Ministry of industry and trade intend to attract leading international experts. Already provided funds the state on researches of tourist potential. Stimulation of further development of international tourism in a country and strengthening of work on presentation of tourist potential of the state in the world tourist market sanctified to hired.